2012
DOI: 10.1074/jbc.m112.357509
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid Protease PARL Mediates the Mitochondrial Membrane Potential Loss-induced Cleavage of PGAM5

Abstract: Background: Mitochondrial rhomboid protease PARL mediates the cleavage of PINK1 in healthy mitochondria. Results: PARL mediates the cleavage of PGAM5 in damaged mitochondria. Conclusion: PARL regulates differential cleavage of PINK1 and PGAM5 depending on the health status of mitochondria. Significance: This is the first implication of stress-dependent regulation of PARL-mediated RIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
214
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(234 citation statements)
references
References 44 publications
17
214
3
Order By: Relevance
“…By dephosphorylating phospho-Ub, this might enhance the accessibility of the Ub chains to DUBs and deubiquitination. One potential candidate is PGAM5, a phosphatase localized at the mitochondria that is released from the mitochondria following dissipation of the mitochondrial membrane potential (Sekine et al 2012;Chen et al 2014). Intriguingly, the presence of PGAM5 is required for PINK1 to accumulate during mitophagy, with a loss of PGAM5 reducing PINK1 levels and impairing mitophagy (Lu et al 2014).…”
mentioning
confidence: 99%
“…By dephosphorylating phospho-Ub, this might enhance the accessibility of the Ub chains to DUBs and deubiquitination. One potential candidate is PGAM5, a phosphatase localized at the mitochondria that is released from the mitochondria following dissipation of the mitochondrial membrane potential (Sekine et al 2012;Chen et al 2014). Intriguingly, the presence of PGAM5 is required for PINK1 to accumulate during mitophagy, with a loss of PGAM5 reducing PINK1 levels and impairing mitophagy (Lu et al 2014).…”
mentioning
confidence: 99%
“…Multiple isoforms of PGAM5 have been reported (5)(6)(7). The predominant isoform of PGAM5, denoted PGAM5-L, encodes a protein of 289 amino acids in which amino acids 98 -289 compose the PGAM domain.…”
mentioning
confidence: 99%
“…Both the long and short isoforms of PGAM5 contain an N-terminal mitochondrial targeting sequence that anchors the protein on the cytosolic face of the outer mitochondrial membrane (8). Proteolytic removal of the mitochondrial targeting sequence, which releases a truncated PGAM5 protein from the mitochondrial membrane, has been implicated in apoptosis and mitophagy (6,7).…”
mentioning
confidence: 99%
“…PGAM5 has been shown to be activated in necroptosis triggering DNM1L dephosphorylation and translocation to mitochondria leading to mitochondria fragmentation (44). In addition, upon mitochondrial membrane potential loss, PGAM5 is cleaved (45), being therefore a good marker for this event. We observed that BIRO1 induced an accumulation of the cleaved PGAM-L isoform.…”
Section: Discussionmentioning
confidence: 99%